University Knowledge Inside: How and When University–Industry Collaborations Make New Products More Attractive to Consumers - Maier, Lukas; Schreier, Martin; Baccarella, Christian V.; Voigt, Kai-Ingo (Journal of Marketing, 2024)
In this research, the authors examine how consumers perceive the fruits of university–industry collaborations (i.e., new products codeveloped with universities). Eight studies document a positive university effect and highlight its practical significance and boundary conditions. An Instagram A/B test utilizing a video that refers (vs. does not refer) to the underlying university–industry collaboration results in higher click-through rates and ad engagement levels. Another field study demonstrates that university-codeveloped products are more attractive to consumers, even after an actual product trial. Further, several consequential studies reveal that consumers are willing to pay up to 65% more for products marketed as codeveloped with a university. The authors argue and show that collaborating with a university infuses the underlying firm with a stronger sense of scientific legitimacy, thereby making the resulting product more attractive to consumers. Congruously, the authors find that the effect is more pronounced when the scientific legitimacy engendered by universities is more important to the focal product (i.e., high tech vs. low tech), underlying company (i.e., new vs. established), or target customer (i.e., high vs. low belief in science).